The butanol producing microbe Clostridium beijerinckii NCIMB 14988 manipulated using forward and reverse genetic tools - Little, Gareth T.; Willson, Benjamin J.; Heap, John T.; Winzer, Klaus; Minton, Nigel P. (Wiley, 2018)
The solventogenic anaerobe Clostridium beijerinckii has potential for use in the sustainable bioconversion of plant-derived carbohydrates into solvents, such as butanol or acetone. However, relatively few strains have been extensively characterised either at the genomic level or through exemplification of a complete genetic toolkit. To remedy this situation, a new strain of C. beijerinckii, NCIMB 14988, was selected from amongst a total of 55 new clostridial isolates capable of growth on hexose and pentose sugars. Chosen on the basis of its favourable properties, the complete genome sequence of NCIMB 14988 was determined and a high-efficiency plasmid transformation protocol devised. The developed DNA transfer procedure allowed demonstration in NCIMB 14988 of the forward and reverse genetic techniques of transposon mutagenesis and gene knockout, respectively. The latter was accomplished through the successful deployment of both group II intron retargeting (ClosTron) and allelic exchange. In addition to gene inactivation, the developed allelic exchange procedure was used to create point mutations in the chromosome, allowing for the effect of amino acid changes in enzymes involved in primary metabolism to be characterised. ClosTron mediated disruption of the currently unannotated non-coding region between genes LF65_05915 and LF65_05920 was found to result in a non-sporulating phenotype.